Variability in Mammography Quality Assessment After Implementation of Enhancing Quality Using the Inspection Program (EQUIP). Issue 2 (23rd January 2021) - Funaro, Kimberly; Niell, Bethany
Abstract: Objective: Analyze mammography quality and deficiencies, including variability in quality assessment among subspecialized breast radiologists, after implementing the Enhancing Quality Using the Inspection Program (EQUIP). Methods: After IRB approval, this single institution study retrospectively queried data prospectively entered into our automated reporting software after implementing EQUIP (October 2017–March 2019). Screening and diagnostic combination (digital mammography with tomosynthesis) mammograms were reviewed by seven breast radiologists. Quality was assessed as excellent, good, adequate, or problems found. Of those with problems found, the deficiency and corrective action were evaluated. The interpreting radiologist, EQUIP radiologist, and performing technologist were recorded. P values were calculated using Fisher exact test and chi-square analyses. Results: Of 17 312 mammograms, 529 (3%) underwent EQUIP review. Of 43 (8%) with problems found, 23 (53%) did not include sufficient tissue, 9 (21%) had motion degradation, 3 (7%) had artifacts, 2 each (4.7% each) had the nipple not in profile or skin folds, and 4 (9%) were categorized as "other." Nine (9/529, 1.7%) required recall for repeat imaging. The lead interpreting physician (LIP) was more likely to categorize mammograms as technically inadequate compared to other radiologists ( P < 0.00001), and there were also statistically significant differences in how the remaining radiologists stratified cases ( P < 0.00001) even when excluding the LIP. Conclusion: Insufficient tissue was the most common problem identified in the EQUIP-reviewed mammograms with deficiencies. Significant variability was present among radiologist EQUIP designations. Ongoing review of clinical image quality with EQUIP allows for opportunities to provide corrective feedback.